A Ciência nos Telejornais Brasileiros (O papel educativo e a compreensão pública das matérias de CT&I) - Alberguini, Audre Cristina (2007)
This work researches the covering of Science, Technology and Inovation (ST&I) on brazilian open channel TV news, at prime time (from 7:15 pm to 10 pm), to notice the educational function of media in the approach of the subjects ST&I. The corpus of this research is made up from a clipping from the following TV news: Jornal da Band, Jornal Nacional, Jornal da Record, Jornal da Cultura and SBT Brasil. The proposal was to evaluate comparatively the journalist subjects that specifically deal with ST&I, in relation to the format, the language and the contents of each studied programs. This work made use of the French Discourse Analysis (DA) Methodology. This quality research also englobed a Study of Reception about the selected reportings. The procedure employed for this was the Focus Groups. This way, it attempted to análise the communication process that covers the news subjects of ST&I from messages to reception. This study noticed that ST&I is present subject on brazilian TV news even if there happen unpredictable facts (from others editorials) that influence significatively the covering of the TV news. It also noticed that there isn´t among the selected TV news a deepening standard and contextualization of ST&I subjects but that the approach varies even involving a single edition. The broadcasting channels, even admitting the importance of ST&I, are still oscillate between a contextualized approach and the simple description of the principal fact. The language used on TV news concerned with the subjects of Science, Tecchnology and Inovation is predominantly clear and simple. Nevertheless it was possible to notice some nuances, with the use of specific terms of the scientific language without the subject offering any explanation about such concepts. The experience of the Focus Groups showed that television viewers are not passive in relation to the scientific contents of the telejournalist programs. In general, people are interested in ST&I and know how to evaluate the subjects qualitatively. Analyzing how the subjects about ST&I make sense and what contribution they can give to the Public Understanding of Science, facilitated important reflections about the limitations and the potencials of television and the linked messages as well as the interest and critical vision in respect to the subjects of ST&I.(AU)